Efficacy of Dexamethasone Adjuvant in Brachial plexus Block – A Comparison with Fentanyl Adjuvant (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Background: In supraclavicular brachial plexus block, local anaesthetics provide good operativeconditions but have shorter duration of post-operative analgesia. Now-a-days different drugs have beenused as an adjuvant with local anaesthetic in brachial plexus block to achieve quick, dense and prolongedblock. Fentanyl is commonly used but this is associated with side effects like nausea, vomiting,sedation,respiratory depression and pruritus. So adjuvant drugs with minimal side effects but produce goodsurgical anaesthesia are always looked for.The benefit of adjuvant dexamethasone has recently been thefocus of investigation as clinical reports suggest improved block characteristics.Objectives:To compare the quality of anaesthesia & the duration of analgesia period betweendexamethasone-bupivacaine combination and fentanyl-bupivacaine combination in supraclavicularbrachial plexus block.Methods:60 adult patients of either sex, aged 18 – 60 years,ASA physical status I or II,posted for electivesurgeries of elbow, forearm and hand under supraclavicular brachial plexus block wereenrolled in thestudy. Patients were randomly allocated to one of the two groups - group A and group B. Group A (n=30)–received 38 mL 0.25% bupivacaine and 2 mL dexamethasone (10 mg). Group B (n=30) –received 38 mL0.25% bupivacaine and 2 mL fentanyl (100mcg). Data were analyzed by Student’s t test and Unpaired ttestas appropriate.Result:Onset of sensory and motor block were significantly higher in group-B than in group-A (P = 0.000)and sensory and motor block were quite prolonged in group-A than group-B (p =0.000). Duration ofeffectiveanalgesia (time from supraclavicular block to first analgesic demand) in study group-A hadsignificantlylonger mean duration than that produced by control group-B (825.59 ± 13.44vs 667.40 ± 23.64 minutes).Conclusion:Dexamethasone and bupivacaine combination is a better alternative to fentanyl andbupivacaine inrespect of quality of anaesthesia and duration of analgesia.JBSA 2019; 32(2): 13-20